Buruh Migran dan Human Trafficking: Studi Tentang Peningkatan Perdagangan Manusia dari Indonesia ke Malaysia - Monique, Pricillia; Puspamawarni, Vita Amalia (Jurnal Transformasi Global, 2020)
Human trafficking is a serious Transnational Organized Crime (TOC) faced by countries globally, including Indonesia and its neighbor, Malaysia. Both countries are categorized as tier 2 in the Palermo Protocol watchlist for their ineffective implementation of national laws and regulations to prevent or stop human trafficking. While Indonesia becomes the source country for human trafficking, Malaysia is the receiving country with the most Indonesian victims of human trafficking. There has been an increasing number of cases in 2014-2016. This paper aims to answer the main research question: what has caused the increase of human trafficking cases between Indonesia and Malaysia within this period? While internal factors from the source country influence human trafficking, external and personal factors contribute to the cases.